Effect of electroacupuncture on the intestinal microflora in rats with stress urinary incontinence - Li, Chaonan; Qu, Zhiyu; Liu, Jiandang; Ruan, Shuoquan; Chen, Bingli; Ran, Jinchuan; Shu, Wen; Chen, Yuelai; Hou, Wenguang (Frontiers in Endocrinology, 2022)
Abstract Objective: To examine the effect of electroacupuncture (EA) on the urodynamics and gut microbiota of stress urinary incontinence (SUI) rats. Materials and methods: Thirty 2-month-old female Sprague-Dawley (SD) rats were randomly assigned to 4 groups: normal (N), model (M), nonacupoint electric acupuncture control (NAAC), and EA. An SUI rat model was established through vaginal balloon dilatation and bilateral oophorectomy. After various treatments, urodynamic tests were performed, and feces were collected. 16S rRNA sequencing analysis was used to investigate SUI-related intestinal flora changes. Results: After treatment, compared with those of the M group, the leak point pressures (LPPs) and maximum bladder capacity (MBC) of the EA groups were increased (P<0.05). The species community compositions of the N and M groups differed at the genus level, and there were 15 differentially abundant bacterial genera (P<0.05). The Blautia proportion was increased by EA treatment (P<0.05), and significantly positively correlated with the EA treatment of SUI (according to Spearman correlation analysis). Conclusion: EA treatment can improve the urine leakage sign of SUI rats by increasing the LPP and MBC. After EA treatment, Blautia enrichment may be related to SUI sign improvement. Keywords: Electroacupuncture; Stress urinary incontinence; Urodynamics; Intestinal flora; Blautia